Effectiveness of support groups to improve the quality of life of people with idiopathic pulmonary fibrosis a pre-post test pilot study - Magnani, Daniela; Lenoci, Graziana; Balduzzi, Sara; Artioli, Giovanna; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Idiopathic Pulmonary Fibrosis (IPF) is an interstitial lung disease, which progressively leads to severe disability and death. The average survival expectancy, ranges from 3 to 5 years from diagnosis, and the available medicines do not lead to healing. The progression of IPF lead to a decline in forced vital capacity (FVC), dyspnea, cough, continuous sleep interruptions, resulting in increased fatigue and deteriorating quality of life (QOL), progressive limitation of daily life activities and social life, with repercussions on psychological and emotional well-being, aggravated by anxiety, loss of sense of self-confidence and depression. The aim of the study was to evaluate how the support groups influence the psychological well-being of people with IPF and their family members. Methods: A pre-post test pilot study with a single group was conducted in a university hospital in Northern Italy, a centre for diagnosis and treatment of IPF. A support group was conducted by a nurse and entirely dedicated to people with IPF and their family members. Eighteen participants were enrolled in the support group. To measure the changes in psychological well-being was chosen the Psychological General Well-Being Index (PGWBI), which was administered at the time of enrolment to the group and after six months of attendance. Results: Even if the effect is not statistically significant, the paired t-test showed that the participation in a support group conducted by a nurse, could increase psychological well-being in all of its dimensions: anxiety, depression, positivity, self-control, overall health, and vitality. Conclusions: Despite the null association, the increase of psychological well-being, closely related to the quality of life, indicates the need to further studies. In the absence of effective pharmacological treatments for healing, the support groups represent an opportunity for the wellbeing of the IPF patients and their caregivers.